SYNTACTIC INTERFERENCE OF KUPANG MALAY INTO INDONESIAN LANGUAGE - Bessie, Polce Aryanto (Prosiding Seminar Nasional Bahasa Ibu; Vol 2 No 1 (2025): Prosiding Seminar Nasional Bahasa Ibu 2024/2025, 2024)
This paper aims at defining the types of interference of Kupang Malay into Indonesian language done by theenagers in Kupang and also examining how the inference occurs. The method applied in this research was descriptive qualitative method. The result indicates that syntactically, the members of Namosain Club undergo language interference, especially in two parts, namely: the Kupang Malay interference into Indonesian language in Phrase level and the Kupang Malay interference into Indonesian language in predicate level. Because Indonesian and Kupang Malay have different pattern in particular phrase level and sentence level, thus it influences the interference in Indonesian. Besides that, Kupang Malay has no affixes as in Indonesian.